Deficiency of retinaldehyde dehydrogenase 1 induces BMP2 and increases bone mass in vivo. - Shriram Nallamshetty; Hong Wang; Eun-Jung Rhee; Florian W Kiefer; Jonathan D Brown; Sutada Lotinun; Phuong Le; Roland Baron; Clifford J Rosen; Jorge Plutzky (PLoS ONE)
The effects of retinoids, the structural derivatives of vitamin A (retinol), on post-natal peak bone density acquisition and skeletal remodeling are complex and compartment specific. Emerging data indicates that retinoids, such as all trans retinoic acid (ATRA) and its precursor all trans retinaldehyde (Rald), exhibit distinct and divergent transcriptional effects in metabolism. Despite these observations, the role of enzymes that control retinoid metabolism in bone remains undefined. In this study, we examined the skeletal phenotype of mice deficient in retinaldehyde dehydrogenase 1 (Aldh1a1), the enzyme responsible for converting Rald to ATRA in adult animals. Bone densitometry and micro-computed tomography (µCT) demonstrated that Aldh1a1-deficient (Aldh1a1(-/-) ) female mice had higher trabecular and cortical bone mass compared to age and sex-matched control C57Bl/6 wild type (WT) mice at multiple time points. Histomorphometry confirmed increased cortical bone thickness and demonstrated significantly higher bone marrow adiposity in Aldh1a1(-/-) mice. In serum assays, Aldh1a1(-/-) mice also had higher serum IGF-1 levels. In vitro, primary Aldh1a1(-/-) mesenchymal stem cells (MSCs) expressed significantly higher levels of bone morphogenetic protein 2 (BMP2) and demonstrated enhanced osteoblastogenesis and adipogenesis versus WT MSCs. BMP2 was also expressed at higher levels in the femurs and tibias of Aldh1a1(-/-) mice with accompanying induction of BMP2-regulated responses, including expression of Runx2 and alkaline phosphatase, and Smad phosphorylation. In vitro, Rald, which accumulates in Aldh1a1(-/-) mice, potently induced BMP2 in WT MSCs in a retinoic acid receptor (RAR)-dependent manner, suggesting that Rald is involved in the BMP2 increases seen in Aldh1a1 deficiency in vivo. Collectively, these data implicate Aldh1a1 as a novel determinant of cortical bone density and marrow adiposity in the skeleton in vivo through modulation of BMP signaling.